Hermite spectral method for solving inverse heat source problems in multiple dimensions. Issue 9 (2nd September 2017) - Meng, Zehong; Zhao, Zhenyu
Abstract : In this paper, we in multiple dimensions. We present a stability estimate for determining the source term in the multiple dimensional heat equation in an unbounded domain, and the regularization parameter is chosen by a discrepancy principle. Error estimate between the exact solution and its regularization solution is given. Numerical experiments for the one-dimension and two-dimension cases show the effectiveness of the method.